2022
DOI: 10.1039/d2qm00028h
|View full text |Cite
|
Sign up to set email alerts
|

Simple, quick and green isolation of cannabinoids from complex natural product extracts using sustainable mesoporous materials (Starbon®)

Abstract: The current process to purify CBD from C. sativa extract is long and intensive, requiring several steps such as winterification for 48 hours at -45 °C and high-temperature, high vacuum...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This study demonstrated that the outputs of 23 US states grouping and cannabis plant samples clustering based on cannabis contents by PCA were sensitive to phytocannabinoids profile, in addition to terpenoids profile. Similar GC‐FID‐based analyses of phytocannabinoids present in C. sativa have been reported by several other researchers 35,37,39,40,42,51,57,58 . A solid‐phase‐extraction (SPE) method coupled with the GC‐FID technique was utilised for the extraction and detection of CBD ( 3 ) from C. sativa .…”
Section: Gc Analysis Of Phytocannabinoidsmentioning
confidence: 61%
See 4 more Smart Citations
“…This study demonstrated that the outputs of 23 US states grouping and cannabis plant samples clustering based on cannabis contents by PCA were sensitive to phytocannabinoids profile, in addition to terpenoids profile. Similar GC‐FID‐based analyses of phytocannabinoids present in C. sativa have been reported by several other researchers 35,37,39,40,42,51,57,58 . A solid‐phase‐extraction (SPE) method coupled with the GC‐FID technique was utilised for the extraction and detection of CBD ( 3 ) from C. sativa .…”
Section: Gc Analysis Of Phytocannabinoidsmentioning
confidence: 61%
“…Starbons A300 was used as the stationary phase in SPE taking C. sativa extract in n-hexane to selectively adsorb the phytocannabinoids onto the surface, followed by ethanol (EtOH) to facilitate desorption at up to 93%. 35 A similar one-pot system using Fedora hemp stem dust as feedstock with extraction and adsorption in supercritical CO 2 followed by desorption in EtOH was also proved to be successful, where a GC-EI-MS was employed; CBC (1), CBD (3), CBG (5), and THC (10) were identified. 35 While the yield of total decarboxylated CBD (3) from percolations and macerations of C. sativa plant materials performed over 2 weeks was determined by GC-FID, 37 Gul et al 39…”
Section: Gc Analysis Of Phytocannabinoids In Plant Samplesmentioning
confidence: 99%
See 3 more Smart Citations